رؤية تحليلية للخطة الخمسية العاشرة ومعالم الخطة الخمسية الحادية عشرة (Latakia University Journal - Economic and Legal Sciences Series, 2019)
انطلقت الخطة الخمسية العاشرة للفترة الزمنية الممتدة من عام2006 ولغاية عام2010, من زيادة مستوى القدرة التنافسية للاقتصاد السوري, من خلال الاستفادة من التقنيات الحديثة, وتراكم الخبرات الوطنية, ورفع مستوى جودة السلع والخدمات المنتجة وطنياً. وركزت الخطة على نقطة محورية تتجسد في الوصول إلى تحقيق التنمية الاقتصادية والعدالة الاجتماعية, بالاعتماد على ركيزتين أساسيتين وهما: السوق وانطلاقتها والدولة وتوجهاتها. من هنا كان السؤال المركزي المطروح في بحثنا يدور حول هل حققت هذه الخطة أهدافها حلال السنوات الأربع الماضية الممتدة بين 2006 و2009. للإجابة على هذا التساؤل قمنا بتحليل المؤشرات الاقتصادية المحققة فعلياً ومقارنتها مع ما هو مخطط, من خلال الدراسة والتحليل توصل الباحث إلى أنّ هناك الكثير من المعوقات التي حالت دون التوصل إلى تحقيق الأهداف المنشودة, فيما يتعلق بمعدل النمو الاقتصادي, ولاسيما في قطاعات الإنتاج المادية كالزراعة والصناعة, أمّا في الجانب الاجتماعي فلم يتم إعطاء نهج اقتصاد السوق الاجتماعي الأهمية الكافية. The 10th quinquennial plan was launched for the period between 2006 till 2010, to increase the competitive ability of the Syrian Economy, be benefiting of the modern technology and the accumulation of national expertise and increase the quality level of the commodities and services produced nationally. The plan focused on a pivotal idea which is achieving the economic development and social justice, depending on two basics: the market and its launching, and the government   The central question was in this research as whether this plan had achieved its objectives in the last four years between 2006- 2010. To answer this question we analyzed the truly achieved economic indices and comparing it with what is being planned, and by the study and the analysis, the researcher concluded that there are many obstacles that prevented from achieving the desired targets, concerning the average of the economic growth, especially in production sectors such as agriculture and industry. But at the social side, the concept of the social market economy the necessary attention.